Compressive properties of additively manufactured functionally graded kagome lattice structure - Gautam, Rinoj (2019)
Cellular lattice structures have important applications in aerospace, automobile and defense industries due to their high specific strength, modulus and energy absorption. Additive manufacturing provides the design freedom to fabricate complex cellular structures. This study investigates the compressive properties and deformation behavior of a Ti-6Al-4V unit Kagome structure fabricated by selective laser melting. Further, the mechanical performance of multi-unit and multi-layer Kagome structure of acrylonitrile butadiene styrene (ABS) ABS-M30™ manufactured by fused deposition modeling is explored. The effect of a number of layers of Kagome structure on the compressive properties is investigated. This paper also explores the mechanical properties of functionally graded and uniform density Kagome structure. The stiffness of the structure decreased with the increase in the number of layers whereas no change in peak load was observed. The functionally graded Kagome structure provided 35% more energy absorption than the uniform density structure.